The Performance of the Tourism Sector Toward FDI Attraction Among Other Sectors of the Ghanaian Economy - Yu Jing; Yeboah Evans; Ohene Gyan Christian (European Scientific Journal, ESJ, 2018)
This paper provides a literature review on the impact of foreign direct investment on economic growth and development of the Ghanaian economy; by considering foreign direct investment contributions on employments creation and the allocation of registered projects to the various sectors based on the data collected from the Ghana Investment Promotion Centre, it was discovered that there was a decline in the number of projects registered by investors in 2015 and an increase in 2017. However, it was also revealed that the tourism sector performance toward the attraction of foreign direct investment and employment generating has been reducing indirectly between 2013 and 2017 of which the tourism sector did not create any employment in 2017. Conversely, there is much focus on manufacturing, service, building & construction and general trading sectors as majority of FDI inflows has been directed into these sectors. It is recommended that investors should enter the neglected sectors since there will be much benefit in these overlooked sectors, whereas the government of Ghana should provide incentives in these undermined sectors.